STRATEGI PEMASARAN USAHA TANAMAN HIAS DI KOTA BATURAJA KABUPATEN OGAN KOMERING ULU - amelia permatasari; munajat munajat (JASEP, 2022)
This study aims to analyze internal factors (strengths and weaknesses) and external factors (opportunities and threats) and analyze the marketing strategy of ornamental plant business in the City of Baturaja, Ogan Komering Ulu Regency. The research method used in this study is the Survey method. The sampling method used in this study is the accidental sampling method, which is the method used by taking the entire population with a total sample of 40 people. The results showed that the internal factors of business marketing of ornamental plants in the form of strength (sellers have expertise in ornamental plant cultivation, strategic location, respondents to buyers, quality of ornamental plants business is good (supervision of AKLI) and weaknesses (minimal capital, simple tools and technology , Marketing management that has not been optimal, Lack of promotional activities), External factors in the form of capital loans from banks, Diverse types of plants, Local government programs, Government attention in the form of guidance and education, and Threats (Prices of ornamental plants continue to decline, Taste consumers pariatif, Ornamental plants are always changing, competitors are traders from outside the OKU area). The marketing strategy for ornamental plants is to improve quality services.Keyword: Revenue, Rice, Pattern Partnership, Pure Pattern